Child-led play for children with Autism Spectrum Disorder (ASD): Lessons learned from Parents: Bermain dipimpin oleh kanak-kanak dengan Autism Spectrum Disorder (ASD): Perspektif Ibu Bapa - Shamsudin, Iylia Dayana (Jurnal Pendidikan Bitara UPSI, 2021)
Play is important for children’s development and used as teaching and learning tool for children. Children’s skills including physical, emotion, social and cognitive are potentially to develop that could transform children into their full potential. Play is effective in supporting children’s development and learning when it is child-directed and focuses on play as the main aim with development and learning as the by-product. Children with Autism Spectrum Disorder (ASD) faced multifaceted challenges and resulted in receiving little benefit from play. This qualitative study through in-depth semi-structured interviews explores parents of children with ASD’s perspectives about child-led play for children with ASD. Analysis of the interviews found that children with ASD were able to engage in child-led play activities at home and showed positive outcomes in their play, social, language and communication skills as well as their prosocial behaviour. Although positive outcomes have been shown, interpretation of the findings should be cautionary due to limited representation of the data for Malaysian population and can be further improved with varied and more participants. Various source of data to be analysed are recommended to increase sensitivity of the finding interpretation.